Dampak Pengembangan Wisata Halal terhadap Kinerja UMKM Lokal di Pangkalpinang - Ulfa, Ulfa; Putra, Agung Rizki (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of halal tourism development on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Pangkalpinang City. Halal tourism development is considered a strategic approach to promoting local economic growth based on Islamic values, involving local business actors as providers of Muslim-friendly products and services. A quantitative approach was used, with a survey conducted among 130 MSME actors engaged in the tourism sector. The data were analyzed using multiple linear regression, along with classical assumption tests and hypothesis testing. The results indicate that halal tourism development has a positive and significant effect on MSME performance, as reflected in increased income, market expansion, and product quality improvement. Government support also plays a crucial role in strengthening infrastructure, regulations, and business empowerment. These findings align with Local Economic Theory and the concept of halal tourism, both of which emphasize the importance of leveraging local resources and religious values for sustainable development. The study recommends strong synergy between the government, MSMEs, and local communities to optimize halal tourism potential as a driver of regional economic growth.